LYC_004: Focus Group Discussions with Ivorian female Highschool students about sex education and school pregnancies (Health Discourses as Moral Communication? Linguistic Case Studies from Côte d'Ivoire and Cameroon, 2021)
Focus Group Discussions with Ivorian female Highschool students about sex education and school pregnancies.
Keywords: Communication; Ethics; Women; Pregnancy; Reproductive health; Africa; Teenage pregnancy; Abortion; Contraception; Prevention; Applied ethics; Birth Control; Moral Communication; Focus Group Discussion; Côte d'Ivoire; Ivory Coast; Adolescent Pregnancy; Morality